2011
DOI: 10.1039/c0ee00294a
|View full text |Cite
|
Sign up to set email alerts
|

A crosslinked “polymer–gel” rechargeable lithium-ion battery electrolyte from free radical polymerization using nonionic plastic crystalline electrolyte medium

Abstract: A cross-linked polymer-gel soft matter electrolyte with superior electrochemical, thermal and mechanical properties obtained from free radical polymerization of vinyl monomers in a semi-solid organic nonionic plastic crystalline electrolyte for application in rechargeable lithium-ion batteries is discussed here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 15 publications
(11 reference statements)
1
24
0
Order By: Relevance
“…This study is representative, as cross-linking and addition of nanoparticles represent the most effective ways to improve the ionic conductivity and mechanical properties. [58,263,267,268] Taking crosslinked GEs as an example, to achieve 3D contact between the electrolyte and electrodes, the preparation of the GE was divided into two steps. Techniques for achieving good contact between a solid electrolyte and electrode particles: a) powder sintering for ISEs, [238,239] b) solution or melt-based mixing [74,240] for SPEs, and c) coating by solution casting, sputtering, or spraying.…”
Section: Gel Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is representative, as cross-linking and addition of nanoparticles represent the most effective ways to improve the ionic conductivity and mechanical properties. [58,263,267,268] Taking crosslinked GEs as an example, to achieve 3D contact between the electrolyte and electrodes, the preparation of the GE was divided into two steps. Techniques for achieving good contact between a solid electrolyte and electrode particles: a) powder sintering for ISEs, [238,239] b) solution or melt-based mixing [74,240] for SPEs, and c) coating by solution casting, sputtering, or spraying.…”
Section: Gel Electrolytesmentioning
confidence: 99%
“…Figure 7 shows one example of this strategy for fabrication of supercapacitor by Huang et al [266] At the same time, the authors proposed a roll-to-roll assembly for supercapacitors, as shown in Figure 7 b. Benefitting from good contact between the electrolyte and the electrodes, the device showed superior per-formance compared to conventional liquid electrolytes, as shown in Figure 7 c and 7 d. In addition, strategies on the design of the structures and fabrication of GEs have also been used to form good contacts. [58,263,267,268] Taking crosslinked GEs as an example, to achieve 3D contact between the electrolyte and electrodes, the preparation of the GE was divided into two steps. Firstly, the electrode was soaked in the liquid mixture containing the monomer, initiator, and liquid electrolyte, secondly, the monomer was cross-linked with the electrode in situ.…”
Section: Gel Electrolytesmentioning
confidence: 99%
“…For the matrix containing unsaturated bonds, the chemically cross-linked framework is usually obtained by free radical cross-linking reaction initiated by heat [3] or ultraviolet light [7,8]. Due to higher mobility of Li + in GPE system, the ionic conductivity of GPE is usually higher than liquid-free solid polymer [9] electrolytes or even similar to traditional liquid electrolytes (10 −3 S/cm) [10,11], such as solution of LiPF 6 in ethylene carbonate/propylene carbonate/dimethyl carbonate [26]. Besides, the safety problems of traditional liquid electrolytes caused by leakage or instability upon cycling can be avoided in the application of GPE [5].…”
Section: Introductionmentioning
confidence: 99%
“…GPE are usually prepared by trapping lithium salt and organic solvent molecules into a cross-linked polymer framework through soaking [2] or blending [3]. In contrast to physically cross-linked GPE [4], chemically cross-linked GPE often exhibit better mechanical properties and avoid solvent leakage at high temperatures because of the chemically bonded tie-points and irreversible gels in the system [5,6]. For the matrix containing unsaturated bonds, the chemically cross-linked framework is usually obtained by free radical cross-linking reaction initiated by heat [3] or ultraviolet light [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Table S2 shows a summary of the electrochemical properties of SPEs with different lithium salts, fillers, and representative solid electrolytes, among of which the poly (ethylene oxide) (PEO) is a most widely studied solid electrolyte since Wright et al reported [6][7][8][9][10][11][12]. The PEO could play as an ionic conductor medium to dissolve electrolyte salt, and the improved electronic and ion conductivity of the SPEs can be obtained by mixing with inorganic fillers and processing the thermal treatment to modify the PEO dipole orientation to protect oligoether-crystallinity of PEO [13,14].…”
Section: Introductionmentioning
confidence: 99%